ANALISIS POTENSI INTERAKSI OBAT ANTIHIPERTENSI PADA PASIEN GERIATRI DI INSTALASI RAWAT JALAN RSUD Dr. ACHMAD MOCHTAR BUKITTINGGI TAHUN 2023 - Yola Gustina Efendi; Deswati, M.Farm.,Apt, Khairil Armal, S.Si.,Apt.,SpFRS (CV. Adiba Aisha Amira, 2025)
Hypertension is a condition in which a person experiences an increase in blood pressure above normal with systolic pressure ≥140 mmHg and diastolic pressure ≥90 mmHg. In the elderly, there is a high risk of hypertension due to decreased organ function, causing comorbidities. Therefore, a combination of several drugs is needed to achieve the target blood pressure. However, the combination of several drugs at once can cause drug interactions. This study aims to determine the potential for drug interactions based on the mechanism of action of the drug, the level of drug interactions and to determine the relationship between comorbidities and the number of R / with the incidence of drug interactions in geriatric hypertensive patients at the Outpatient Installation of Dr. Achmad Mochtar Hospital Bukittinggi. The study was conducted retrospectively with data sources from medical records and prescription sheets of geriatric hypertensive patients at the Outpatient Installation of Dr. Achmad Mochtar Hospital from January to December 2023. Sampling was carried out using a purposive sampling technique and the number of samples that met the inclusion criteria was 71 patients. Identification of drug interactions was carried out using the interaction checker drugs.com, Medscape, and stockley's e book. Based on the results of the study in obtained the potential for drug interaction events as much as 91.5% with the highest level of drug interaction, namely moderate as much as 56% with the most drug interaction mechanisms, namely pharmacodynamics as much as 75.8%. This study shows a relationship between comorbidities and the number of R / with the occurrence of drug interactions with a significant value (p <0.05).